SCHWANN AMS 12,017, Geistliche Gesänge aus Dahomey (Christian Songs from Dahomey), a 7" 33? r.p.m. mono record, cost DM 8,- presents Christianized Hanyä songs from Dahomey. (International Library of African Music, 1968)
pages: 66
Keywords: African Music